Effects of Calsporin® on Turkey Performance, Carcass Yield and Nitrogen Reduction - Blair, E.C.; Allen, H.M.; Brooks, S.E.; Firman, J.D.; Robbins, D.H.; Nishimura, Koichi; Ishimaru, Hajime (International Journal of Poultry Science, 2003)
Calsporin®, a probiotic that contains a strain of Bacillus subtilus in a spore form, has been used to increase performance of several species. An experiment was conducted to determine the effects of Calsporin® addition on gain, feed conversion, nitrogen excretion, and salmonella spp. count from the intestinal tract compared to a commercial antibiotic (Bacitracin-Zinc) in male turkeys to market age. Six hundred Hybrid large white tom poults were purchased from a commercial hatchery at day of hatch and randomly allotted into 24 pens, blocked by treatment. Treatments consisted of Calsporin® added at 30 grams per ton of the diet , Bacitracin-zinc at 50 grams per ton or no additive. Birds were housed in an industry standard curtain-sided barn on used pine shavings. Standard corn, soybean meal, animal by-product diets where used for all treatments with nutrient levels based on the 1994 NRC requirements for turkeys. Individual bird weights and pen feed consumption where collected at 21, 42, 63, 84, 105, 126 days. Daily mortality was collected and feed:gain was adjusted to account for mortality. Litter samples where taken from ten random pens at day 63. At 126 days of age three toms per pen where selected based on average pen weight and processed the following day to determine carcass and parts yield. Data were analyzed by analysis of variance (ANOVA) with a randomized block design using the general linear model. By week 12 the treatments that contained either Calsporin® or Bacitracin-zinc had a significantly (p < 0.05) improved gain compared to the treatment without either of the products . For the 0 to 15 and 0 to 18 week phases the birds without additives gained significantly (p< 0.05) less weight compared to all other treatments. No differences in feed efficiency, yield or mortality were observed. Litter samples indicated a reduction in ammonia volitization in Calsporin® fed birds. These data would indicate that Calsporin® may be used successfully as an antibiotic replacement in market turkeys.